Cosmic ray exposure ages for ureilites—New data and a literature study. (29th March 2019) - Leya, Ingo; Stephenson, Peter C.
Abstract: We report newly measured noble gas isotopic concentrations of He, Ne, and Ar for 21 samples from the 10 ureilites, DaG 084, DaG 319, DaG 340, Dho 132, HaH 126, JaH 422, JaH 424, Kenna, NWA 5928, and RaS 247, including the results of both single and stepwise heating extractions. Cosmic ray exposure (CRE) ages calculated using model calculations that fully account for all shielding depths and a wide range of preatmospheric radii, and are tailored to ureilite chemistry, range from 3.7 Ma for Dho 132 to 36.3 Ma for one of several measured Kenna samples. In a Ne‐three‐isotope plot, the data for DaG 340 and JaH 422 plot below the Necos /Neureilite mixing envelope, possibly indicating the presence of Ne produced from solar cosmic rays. In combination with literature data and correcting for pairing, we established a fully consistent database containing 100 samples from 40 different ureilites. The CRE age histogram shows a trend of decreasing meteorite number with increasing CRE age. We speculate that the parent body of the known ureilites is moving closer to a resonance and/or that there is a loss mechanism that acts on ureilites independent of their size. In addition, there is a slight indication for a peak in the range 30 Ma, which might indicate a larger impact on the ureilite daughter body. Finally, we confirm earlier results that the majority of the studied ureilites have relatively small preatmospheric radii less or equal 20 cm.